Hydrodehalogenation of haloarenes by a sodium hydride-iodide composite - Ong, Derek Yiren (2022)
A simple protocol for hydrodebromination and -deiodination of halo(hetero)arenes was enabled by sodium hydride (NaH) in the presence of lithium iodide (LiI). Mechanistic studies showed that an unusual concerted nucleophilic aromatic substitution operates in the present process.